PENERAPAN KODE HUFFMAN PADA ALGORITMA RSA (RIVEST-SHAMIR-ADLEMAN) UNTUK MENYANDIKAN PASSWORD EMAIL - Shofwan Ali Fauji; Mohammad Syaiful Pradana; Niken Ayu Azhari (Unisda Journal of Mathematics and Computer Science (UJMC), 2016)
Email password is highly condential, that the email password can not be seen by other people then the encryption with the science of cryptography. To avoid unwanted things on the email password, the authors will examine and discuss about cryptography or encryption. Encoding using ASCII code and Huffman codewill be applied to the RSA, in order to determine which code is faster in the prosess of encoding the email password. After doing some tests it can be concluded that the Huffman code faster in the encoding process of the ASCII code. The average difference is 45% faster than the ASCII code.